Users’ experiences of a pragmatic diabetes prevention intervention implemented in primary care: qualitative study - Thomas Yates; Joe Kai; Navneet Aujla; Helen Dallosso (BMJ Open)
Objectives To explore service-user and provider experience of the acceptability and value of the Let’s Prevent Diabetes programme, a pragmatic 6-hour behavioural intervention using structured group education, introduced into primary care practice.Design Qualitative interview-based study with thematic analysis.Setting Primary care and community.Participants Purposeful sample of 32 participants, including 22 people at high risk of diabetes who either attended, defaulted from or declined the intervention; and 10 stakeholder professionals involved in implementation.Results Participants had low prior awareness of their elevated risk and were often surprised to be offered intervention. Attenders were commonly older, white, retired and motivated to promote their health; who found their session helpful, particularly for social interaction, raising dietary awareness, and convenience of community location. However attenders highlighted lack of depth, repetition within and length of session, difficulty meeting culturally diverse needs and no follow-up as negative features. Those who defaulted from, or who declined the intervention were notably apprehensive, uncertain or unconvinced about whether they were at risk of diabetes; sought more specific information about the intervention, and were deterred by its group nature and day-long duration, with competing work or family commitments. Local providers recognised inadequate communication of diabetes risk to patients. They highlighted significant challenges for implementation, including resource constraints, and facilitation at individual general practice or locality level.Conclusions This pragmatic diabetes prevention intervention was acceptable in practice, particularly for older, white, retired and health-motivated people. However, pre-intervention information and communication of diabetes risk should be improved to increase engagement and reduce potential fear or uncertainty, with closer integration of services, and more appropriate care pathways, to facilitate uptake and follow-up. Further development of this, or other interventions, is needed to enable wider, and more socially diverse, engagement of people at risk. Balancing a locality and individual practice approach, and how this is resourced are considerations for long-term sustainability.